A fluorescent probe strategy for the detection and discrimination of hydrogen peroxide and peroxynitrite in cells. Issue 76 (7th September 2022) - Bolland, Hannah R.; Hammond, Ester M.; Sedgwick, Adam C.
Abstract : We report a fluorescent probe strategy that provides the potential to detect and discriminate hydrogen peroxide and peroxynitrite in cells. Abstract : Aryl boronate fluorescent probes allow the non-invasive study of dynamic cellular processes involving the reactive species, hydrogen peroxide (H2 O2 ) and peroxynitrite (ONOO − ). However, the ability of these probes to differentiate between these two species remains unclear. Here, we report a boronate-functionalised hemicyanine dye (HD-BPin ) as a potential strategy to distinguish between H2 O2 at 704 nm (red channel) and ONOO − at 460 nm (blue channel) in solution and in cells. This work also highlights the choice of fluorophore before boronate functionalization can dictate the observed selectivity between these two species.